Religiusitas dan Kehidupan Sosial Keagamaan - Najtama, Fikria (Tasamuh: Jurnal Studi Islam, 2017)
Islam is a universal and timeless religion. Islam is not a religion that only guarantees the improvement and enhancement of personal life. Islam is not a religion consisting of dogma, worship and ceremonies. Actually it is a complete way of life, guiding people in accordance with instructions given by God to His Messenger, Muhammad. Islam is a system and a rule of life that includes everything that does not let any one field of human existence to be organized by the forces of Satan. Thus, it is manifested through religious forms religiosity a Muslim. Religiosity is embodied in various sides of human life. Religions not only occur when a person commits ritual behavior (worship), but when do other activities that are encouraged by the strength of the end. Not only with respect to activity that looks and eye can see, but also the activity is not visible and assorted hand or a person. Therefore, religious person will include a wide variety of side or dimension.